Short-long term near infrared spectroscopy patterns after different milk regimens olfactory stimuli in late preterms - Caterina Di Battista; Alice Grometto; Mariachiara Strozzi; Ebe D’Adamo; Giuseppe Lapergola; Antonio Maconi; Claudia Pelazzo; Marta Pasino; Vincenzo Salvo; Francesca Gazzolo; Martina Spinelli; Marta Betti; et al. (Italian Journal of Pediatrics)
Abstract Background The aim of the study is to investigate the effects of olfactory stimuli from breast and formula milk on near-infrared spectroscopy (NIRS) cerebral and splanchnic patterns in late preterm infants. Methods We conducted a multicenter prospective observational pretest-test study in 30 late preterm infants subjected to olfactory stimuli from breast and formula milk. Regional oxygenation status, tissue function in cerebral and splanchnic districts, and cerebral-splanchnic hemodynamic redistribution were recorded at four pre-determined time-points: before sniffing (30 min), during sniffing (30 s), short-term (30 min), and long-term after olfactory stimuli (180 min). Results After olfactory stimuli from breast and formula milk we found: (i) a significant increase (p < 0.05) in cerebral oxygenation and cerebral-splanchnic hemodynamic redistribution after breast milk stimulus, (ii) a significant increase (p < 0.05) in splanchnic oxygenation and splanchnic-cerebral hemodynamic redistribution after formula milk stimulus. Conclusions The present results show early changes in NIRS patterns in cerebral and splanchnic districts after breast and formula milk stimuli. Data opens the way to further studies using NIRS as a reliable tool for central nervous system and splanchnic development and response after olfactory stimuli.